Blood lipids and prostate cancer: a Mendelian randomization analysis. (19th March 2016) - Bull, Caroline J.; Bonilla, Carolina; Holly, Jeff M. P.; Perks, Claire M.; Davies, Neil; Haycock, Philip; Yu, Oriana Hoi Yun; Richards, J. Brent; Eeles, Rosalind; Easton, Doug; Kote‐Jarai, Zsofia; Amin Al Olama, Ali; et al.
Abstract: Genetic risk scores were used as unconfounded instruments for specific lipid traits (Mendelian randomization) to assess whether circulating lipids causally influence prostate cancer risk. Data from 22, 249 prostate cancer cases and 22, 133 controls from 22 studies within the international PRACTICAL consortium were analyzed. Allele scores based on single nucleotide polymorphisms (SNPs) previously reported to be uniquely associated with each of low‐density lipoprotein (LDL), high‐density lipoprotein (HDL), and triglyceride (TG) levels, were first validated in an independent dataset, and then entered into logistic regression models to estimate the presence (and direction) of any causal effect of each lipid trait on prostate cancer risk. There was weak evidence for an association between the LDL genetic score and cancer grade: the odds ratio (OR) per genetically instrumented standard deviation (SD) in LDL, comparing high‐ (≥7 Gleason score) versus low‐grade (<7 Gleason score) cancers was 1.50 (95% CI: 0.92, 2.46; P  = 0.11). A genetically instrumented SD increase in TGs was weakly associated with stage: the OR for advanced versus localized cancer per unit increase in genetic risk score was 1.68 (95% CI: 0.95, 3.00; P  = 0.08). The rs12916‐T variant in 3‐hydroxy‐3‐methylglutaryl‐CoA reductase (HMGCR) was inversely associated with prostate cancer (OR: 0.97; 95% CI: 0.94, 1.00; P  = 0.03). In conclusion, circulating lipids, instrumented by our genetic risk scores, did not appear to alter prostate cancer risk. We found weak evidence that higher LDL and TG levels increase aggressive prostate cancer risk, and that a variant in HMGCR (that mimics the LDL lowering effect of statin drugs) reduces risk. However, inferences are limited by sample size and evidence of pleiotropy. Abstract : Using a Mendelian randomization framework, we have found some evidence to suggest an association between low‐density lipoprotein and triglycerides and more clinically severe PCa, but no evidence between high‐density lipoprotein and these outcomes. There is an unmet clinical need to distinguish between indolent PCas and those that will progress to impact a man's life. Our findings indicate that blood lipids may be involved in this distinction.